Writing motivation: A validation study of self-judgment and performance - Ling, Guangming; Elliot, Norbert; Burstein, Jill C.; McCaffrey, Daniel F.; MacArthur, Charles A.; Holtzman, Steven (Assessing writing, 2021)
•Presents a writing motivation survey.•Establishes a survey internal structure.•Illustrates relationships between survey and indicators of student success.•Offers pedagogical interventions targeting motivation and writing feature use. This study reports on validation of a writing motivation survey and its relationship with a variety of indicators of academic performance of 566 undergraduate students drawn from six US postsecondary institutions. A writing motivation survey was used to capture students’ writing goals, confidence, beliefs, and affect. Two research questions are addressed in the study: 1) What is the internal factor structure of the writing motivation survey completed by a broad range of college students? (2) Using this factor structure, how are the subconstructs of writing motivation associated with the outcomes variables of student performance and features of student writing? Our results confirmed a unidimensional structure for confidence and affect, a 3-factor structure for goals, and a 2-factor structure for beliefs. Low level but significant correlations were also identified between motivation and outcome performance measures, as well as between motivation and features of student writing. The study findings yield insights about the relationship between students’ writing motivation, college success indicators, and writing domain knowledge. These findings suggest directions for pedagogical interventions targeting both motivation and writing feature use.